Control interno del cuerpo de bomberos cantón Valencia de la provincia de Los Ríos, año 2013 - Carrazco Garay, Natalia Del Rocio (2013)
In the research was raised as aims: Assess internal control in the fire of Valencia canton, year 2013, analyzing the structure of organizational and functional fire body of Valencia canton, to establish the processes of administrative areas and accountant, issuing a report of internal control of the results and design a manual of internal control for the institution. The thesis proposal is extremely practical and functional in the scope of the business of services, since the results will contribute to the development of the Elena institution, as well as those organizations in similar situations, since it constitutes a model of immediate solution through the application of an assessment of the internal control that promotes efficiency and effectiveness in the development of operations providing a degree of reasonable safety and proper development of the administrative and accounting procedure in the State. It also responds to discuss goals and objectives formulated and that allows determining weaknesses competitive, establish potential risks, reliability of financial information and strengthening confidence with the compliance of laws and regulations that are applicable to the public sector. The communication of results is detailed internal control report where conclusions and recommendations that will maintain and improve the operation of the administrative and accounting activities of the institution are established and establishes non-compliance with internal control standards and the absence of a manual functions that regulate activities carried out by the staff of the entity Concluded the consideration of internal control is to carry out the respective findings, discussion and recommendations of the results obtained, which is defined in clear and synthetic manner all the observations and recommendations to continue with the process launched that demonstrated in the period of application of this practice the efficiency of response to the multiple challenges that arise every day, and that by having this tool will have the administration of the body fire of the canton of Valencia the opportunity to take decisions that will allow you to grow facing the challenges and common challenges to be exposed.